PERSPEKTIF HUKUM INTERNASIONAL DALAM KASUS ASIAN HATE DI AMERIKA SERIKAT - Natalia, Christine; Utari, Anak Agung Sri (Kertha Semaya : Journal Ilmu Hukum; Vol 10 No 10 (2022), 2022)
Tulisan ini dilatarbelakangi dari efek kasus yang terjadi di Amerika Serikat (AS) yaitu terkait kasus ujaran kebencian kepada orang Asia maupun keturunannya yang dikenal dengan istilah Asian Hate yang mendapat kecaman dari berbagai pihak internasional. Diharapkan tulisan ini mampu menambah wawasan dan pemahaman setiap kita terkait isu persoalan sosial di Amerika Serikat menurut hukum internasional. Studi ini nantinya akan menggunakan metode penelitian normatif dengan pendekatan peraturan perundang-undangan (statute approach), pendekatan kasus ( case approach ), dan pendekatan historis ( historical approach ) . Hasil tulisan ini menunjukkan berdasarkan International Convention on the Elimination of All Forms of Racial Discrimintion (ICERD) dan Universal Decrlaration on Human Rights (UDHR) sendiri sudah lebih dulu menyatakan bahwa setiap manusia harus diperlakukan tanpa diskriminasi. This paper is based on the effect of cases that occurred in the United States (US), namely related to cases of hate speech to Asians and their descendants known as Asian Hate which received criticism from various international parties. This paper will bring more knowledge and awareness that occurred in the United States (US), namely related to cases of hate speech to Asians and their descendants are known as Asian Hate which received criticism from various international parties. This paper will give us further insight into the social and legal issues occurring in the United States according to international law. The paper will eventually adopt a normative-law study method with a constitutional approach, case approach, and historical approach. The results of the paper have shown that based on International Convention on the Elimination of All Forms of Racial Discrimintion (ICERD) and Universal Decrlaration on Human Rights (UDHR) itself, it has been stated that every human being must be treated without discrimination.